Preliminary Study on the Synthesis of Silica Dioxide Using CoconutFibre Ash(CFA) - Jeyaseelan, Deertanan (IRC, 2021)
In this work, waste coconut fiber was explored as potential raw material for silica production. Coconut fiber was burned in controlled environment inside electricalfurnace at 600, 700 and 800 °C.